Have maintenance rituximab and RIC allograft blown away the need for autografts in follicular lymphoma? (Hematology Meeting Reports, 2009)
There is a possibility that despite the long term follow up data on traditional protocols; some patients with follicular lymphoma are now curable, perhaps with transplantation and perhaps without. We have known for some time that radiation therapy may cure some patients with localised disease, and the evidence from anti CD20 antibodies, sometimes given with conventional chemo-therapy, sometimes to eliminate minimal residual disease and sometimes in the radio labelled situation pre transplant, clearly now shows a further incremental reduction in the bulk of the disease beyond traditional conventional therapy. In addition, Registry data for autograft and allograft, the low treatment related mortality of mini allograft and the minimal relapse in patients after so called “conventional” allograft all serve as additional information that relapse can be reduced. The advent of maintenance rituximab proven in a randomised trial may vitiate the need for other approaches such as autograft if it produces fewer relapses.